Energy and Environmental Efficiency Evaluation of Transportation Systems in China’s 255 Cities - Jiao, Liudan; Wu, Fengyan; Luo, Fenglian; Zhang, Yu; Huo, Xiaosen (Frontiers in Environmental Science, 2022)
China’s transportation sector suffers from excessive energy consumption and serious pollutant emissions. There is increasing pressure to improve energy and environmental efficiency (EEE). This paper researches the EEE of transportation systems in 255 Chinese cities from 2015 to 2019 with the assistance of the super-efficiency SBM model. Research results show that the five-year average EEE of the Chinese transportation system is 0.4420, indicating an overall low performance, with most regions still needing improvement. There are significant differences in the transportation system EEE between cities, with Guangzhou, Maoming, and Zhoushan ranking in the top three, and Heihe, Xining, and Taiyuan in the bottom. Cities with a better economic base, developed water systems and more relevant policy documents do better in energy use and environmental protection compared to other cities. Moreover, the development of the transportation systems is uneven, with noticeable regional differences. The general trend is that cities located in the eastern have better transportation systems EEE than cities in other economic zones. The findings should have a far-reaching impact on the sustainable development of cities. It also provides an essential reference for the research on EEE efficiency of transportation systems in China and other countries.